An overview of cooling of thermoelectric devices. (October 2017) - Sajid, Muhammad; Hassan, Ibrahim; Rahman, Aziz
Abstract: Thermoelectric generators are an environmentally friendly source of electrical power whose applications range from waste heat recovery to conversion of solar energy into electricity. Low conversion efficiencies however inhibit their wide scale deployment. Research into thermoelectrics has therefore primarily focused on improvement of material properties, leading to remarkable progress in the area which has not translated into high performing thermoelectric generators. System level efficiency is significantly dependent on effective thermal management. Heat dissipation mechanisms employed to remove waste heat from the cold side of a thermoelectric device are reviewed in this work. The prevalent methods of cooling thermoelectric devices are categorized and based on published experimental data, their contribution on the overall conversion efficiency of thermoelectric generators is quantified. A broad range of devices from low heat to high thermal flux have been covered in this work and will help guide future endeavors in thermoelectric generator design and testing.